Microscale Chemistry Experiments For Upper Secondary Schools In Malaysia - Abdullah, Mashita (2011)

(untitled)
Laboratory work is essential to assist students in acquiring scientific and thinking skills and experience, as well as appreciate chemistry in real life. Students require the hands-on practical and personal laboratory experience. Chemistry practical classes in Malaysian secondary schools are conducted mostly in groups (2 or more), as demonstrations or not conducted at all. Increase in the number of students leads to increased costs of conducting laboratory experiments and also to increase in chemical wastes generated which contributes to environmental pollution.